Leiomyosarcoma in the Nasopharynx: MR Imaging Findings - Kuo, R. (AJNR Am J Neuroradiol, 2007)
SUMMARY: The MR imaging findings of a leiomyosarcoma arising from the nasopharynx are presented. To our knowledge, this is the first MR imaging description of this entity.